The staircase in the woods [large type] - Wendig, Chuck (Del Rey, an imprint of Random House, 2025)
"Five high school friends are bonded by an oath to protect one another no matter what. Then, on a camping trip in the middle of the forest, they find something extraordinary: a mysterious staircase to nowhere. One friend walks up-and never comes back down. Then the staircase disappears. Twenty years later, the staircase has reappeared. Now the group returns to find the lost boy-and what lies beyond the staircase in the woods. . . ." --